DIAGNOSIS OF TRAINING NEEDS IN RURAL TOURISM COMPANIES IN THE CANTON OF COTACACHI - Izurieta, Paúl Oña; Alencastro, Francisco Vaca; Ruiz, Paola Enriquez (Seven Editora, 2024)
The tourism industry in Ecuador needs to have a scientific basis, according to its development and economic growth. According to the Plan for the Creation of Opportunities 2021 - 2025, the government has structured a policy aimed at strengthening the tourism system, therefore, the inquiry carried out with local business representatives will allow us to understand where to direct administrative tools and concrete actions with management models in tourism services. which will seek to promote a culture of quality and good service. The purpose of this scientific article is to make a diagnosis of training needs of technical and administrative skills for the management of the tourist service of the parish of San Francisco and the Sagrario of the Cotacachi Canton of the province of Imbabura. To this end, it is proposed to develop a situational diagnosis, which evidences the reality of tourism service provider companies; and that allows this research to become a significant contribution to the canton. DOI:https://doi.org/10.56238/sevened2024.037-016